Teknologi Calon Guru Sekolah Dasar Dalam Menggunakan Rasch Model - Rara Azwita; Miftahul Jannah (Universitas Maritim AMNI Semarang, 2023)
Knowledge of mathematics, didactics, and technology that must be owned by pre-service and in-service teachers, previously measured by the classical test theory (CTT), but has limitations. Study aims to determine that knowledge with a more accurate prediction method using the item response theory (IRT) from the Rasch model. Study used a survey of mathematical and didactic knowledge, and a survey of technological knowledge with a scale. The subjects were 38 second- year students from an elementary school teacher education institution in Pekanbaru. This study indicates that pre-service teachers have relatively sufficient mathematics and technological knowledge, but they were lack of didactic knowledge. Analysis of pre-service teachers’ knowledge using the Rasch model can provide an overview of the difficulty level of the items given, the level of pre-service teachers’ knowledge, and the interaction between respondents and between questions. Institutions need to develop learning instruction for pre-service teachers that can support the strengthening and development of their mathematical, didactic, and technological knowledge.